The importance of retranslation in drama plays. The case of En attendant Godot - Álvarez Jurado, Manuela; Pérez Geijo, Lorena (Estudios de Traducción, 2025)
Retranslation is the process of translating a text, either in whole or in part, that has already been translated. This practice allows for the adaptation of a piece of text to the current world and society. This is especially relevant in the case of dramatic plays, since theatre relies on orality to a greater extent than the other literary genres.Waiting for Godot is a play of the Theatre of the Absurd that premiered in 1952, written by Samuel Beckett. Although not so much time has passed since it was first published, five Spanish translations were produced between 1953 and 1981. The aim of this paper is to compare three of these five translations in order to highlight the variations between the different versions and to decide about the necessity of a new retranslation.
Keywords: Waiting for Godot; Samuel Beckett; retranslation; Theatre of the Absurd; drama translation